The synthesis and spectroscopy of dipyrrins and their metal complexes : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemistry, Massey University - McLean, Tracey Maree (Massey University, 2012)
Dipyrrin ligands can be considered as ‘half-porphyrins’. They absorb light in the visible region due to a strongly allowed π-π* transition. With the energy crisis being one of the most important issues of our time, the strong absorption in the visible region endows dipyrrinato complexes with promise in solar energy conversion applications. The focus of this project was to undertake some fundamental synthesis and spectroscopy of dipyrrin ligands and dipyrrinato complexes for their applications in photochemical devices. The well-known characteristics of Ru(II)-bipyridine chemistry were combined with the light absorbing properties and synthetic versatility of dipyrrin ligands to prepare and test a range of Ru(II)-dipyrrinato-bipyridine complexes as dyes for applications in dye-sensitised solar cells. The preliminary results of the solar cell measurements show evidence that the Ru(II)-dipyrrinato-bipyridine complexes show promise as light harvesters in solar energy conversion applications. A series of Re(I)-dipyrrinato complexes has also been designed and prepared for potential applications as catalysts in carbon dioxide reduction. Metallodipyrrin complexes also exhibit strong exciton coupling. A library of transition metal dipyrrinato complexes has been prepared to investigate the exciton interactions in dipyrrin systems. Understanding the exciton interactions in dipyrrin systems and the ability to control the exciton interactions are desirable for improving the solar energy conversion efficiency of dye-sensitised solar cells containing Ru(II)-dipyrrinato-bipyridine complexes as the dye. Raman spectroscopy and more specifically resonance Raman, as a technique for probing the excited state of dipyrrinato complexes, has largely been overlooked in the literature. Therefore the spectroscopy aspect of this thesis has a central focus on the Raman spectroscopy of dipyrrins, including the first full characterisation of dipyrrin ligands by Raman spectroscopy at a variety of wavelengths (visible and near infrared). Strong resonance enhancement was observed for the dipyrrin ligands, which lays the foundation for fundamental single-molecule SERS studies but also for a broad range of bioanalytical applications.
Keywords: Dipyrrins; Dipyrrin ligands; Solar energy; Solar cells; Raman spectroscopy; Dipyrrinato complexes